極域成層圏の顕著な気温変動イベントとその長期変動メカニズムの解明 - 西井, 和晃; NISHII, Kazuaki (三重大学, 2017)
application/pdf 冬季北極域の成層圏の気温は数日で数10度も上昇するような現象が発生する一方、普段よりも顕著に気温が低下する現象も発生する。本研究では過去に観測された顕著な気温上昇事例と低下事例を抽出し、それぞれを持続期間によって分類した。その持続期間は対流圏から上向き伝播してくる惑星波の強弱の持続期間に依存し、かつその強弱は特定の地域の対流圏の大気循環変動の存在に大きく影響を受けていることが明らかとなった。また惑星波の強弱に影響する西太平洋パターンの持続過程について明らかにした。また複数の境界条件のもとでの大気大循環モデル実験により成層圏気温長期変動の要因の調査し、北太平洋の海洋前線変動の影響を示唆した。 In winter, temperatures in the Arctic stratosphere experience large variability. The duration of each extreme temperature event differs from event to event, and the frequency of those extreme events shows decadal-scale variability. We classified stratospheric extreme events into short and long events, and found that the duration is dependent on the duration of associated incoming planetary waves from the troposphere. The intensity of the planetary waves depends on tropospheric local circulation anomalies in particular domains. We investigated the mechanism of the Western Pacific pattern that affects the intensity of planetary waves. We also performed ensemble experiments of an atmospheric general circulation model to investigate factors that affect the Arctic stratosphere under various boundary conditions. We found that the midlatitude oceanic front can be one of such factors. 2013年度～2016年度科学研究費補助金(若手研究(B))研究成果報告書 25800261 research report